2018
DOI: 10.1155/2018/2630480
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Newly Prepared Biodegradable 32P-chromic Phosphate-polylactide-co-glycolide Seeds and Their Therapeutic Response Evaluation for Glioma Brachytherapy

Abstract: 32P high-dose rate brachytherapy allows high-dose radiation delivery to target lesions with less damage to adjacent tissues. The early evaluation of its therapeutic effect on tumours is vital for the optimization of treatment regimes. The most commonly used 32P-CP colloid tends to leak with blind therapeutic area after intratumour injection. We prepared 32P-chromic phosphate-polylactide-co-glycolide (32P-CP-PLGA) seeds with biodegradable PLGA as a framework and investigated their characteristics in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Similar to MRI, radionuclide imaging has high sensitivity with no tissue-penetration limitations. Several radionuclide compounds have been extensively studied along with PLGA with the goal of formulating a robust nano delivery system [107]. For instance, Wang and colleagues [108] designed PLGA-lipid hybrid nanocarriers for theranostic therapy, encapsulating an anticancer agent in the matrix, while the lipid shell was chelated with indium-111 or yttrium-90 as radiotherapy agents.…”
Section: Plga Nps For Theranostic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to MRI, radionuclide imaging has high sensitivity with no tissue-penetration limitations. Several radionuclide compounds have been extensively studied along with PLGA with the goal of formulating a robust nano delivery system [107]. For instance, Wang and colleagues [108] designed PLGA-lipid hybrid nanocarriers for theranostic therapy, encapsulating an anticancer agent in the matrix, while the lipid shell was chelated with indium-111 or yttrium-90 as radiotherapy agents.…”
Section: Plga Nps For Theranostic Applicationsmentioning
confidence: 99%
“…For instance, Wang and colleagues [108] designed PLGA-lipid hybrid nanocarriers for theranostic therapy, encapsulating an anticancer agent in the matrix, while the lipid shell was chelated with indium-111 or yttrium-90 as radiotherapy agents. Shao et al [107] demonstrated the therapeutic effect of 32P-CP-PLGA brachytherapy for glioma with the integrin αvβ3-targeted radiotracer 68Ga-3PRGD2. Press and colleagues [109] demonstrated the cell-type-specific delivery of short interfering RNAs by covalent conjugation of DY-635 fluorescent dye with known hepatobiliary clearance to a PLGA, which allowed them to monitor distribution, uptake, and clearance of short hairpin RNA from the target organ.…”
Section: Plga Nps For Theranostic Applicationsmentioning
confidence: 99%
“…Radiolabeling can further enhance the assessment of effects of therapy by brain imaging. For example, 32 p (phosphorus-32)-chromic phosphate-polylactide-co-glycolide (32P-CP-PLGA) for controlled release of the isotope, combined with radiotracer 68 Ga-3PRGD 2 , which targets integrin αvβ3 receptors or the tumor as well as neovasculature, has shown promising results of brachytherapy in a rat model of transplanted glioblastoma ( 65 ).…”
Section: Innovations In Radiotherapymentioning
confidence: 99%